Three-Dimensional Freehand Ultrasound Strain Elastography Based on the Assessment of Endogenous Motion: Phantom Study - SAKALAUSKAS, Andrius; JURKONIS, Rytis; LUKOŠEVIČIUS, Arūnas (Archives of Acoustics, 2023)
The purpose of this paper is to present the results of the pilot experiments demonstrating proof of concept of three-dimensional strain elastography, based on freehand ultrasound for the assessment of strain induced by endogenous motion. The technique was tested by inducing pulsatility in an agar-based tissue mimicking phantom with inclusions having different stiffness and scanning the 1D array with an electromagnetic position sensor. The proof of concept is explored with a defined physical phantom and the adopted algorithm for strain analysis. The agar-based phantom was manufactured with two cylindrical inclusions having different stiffness (7 kPa and 75 kPa in comparison to the background 25 kPa) and scattering properties. The internal strain in the phantom was introduced by mimicking a pulsating artery. The agar mixture displacements were estimated by using the GLUE algorithm. The 3D isosurfaces of inclusion from rendered volumes obtained from the B-mode image set and strain elastograms were reconstructed and superimposed for a quantitative comparison. The correspondence between the B-mode image-based inclusion volume and the strain elastography-based volume was good (the Jaccard similarity coefficient in the range 0.64–0.74). The obtained results confirm the 3D freehand endogenous motion-based elastography as a feasible technique. The visualization of the inclusions was successful. However, quantitative measurements showed that the accuracy of the method in volumetric measurements is limited.